2007
DOI: 10.1002/jts.20258
|View full text |Cite
|
Sign up to set email alerts
|

Anger, hostility, and aggression among Iraq and Afghanistan war veterans reporting PTSD and subthreshold PTSD

Abstract: Iraq and Afghanistan War veterans were grouped by level of posttraumatic stress disorder (PTSD) symptomatology and compared on self-report measures of trait anger, hostility, and aggression. Veterans who screened positive for PTSD reported significantly greater anger and hostility than those in the subthreshold-PTSD and non-PTSD groups. Veterans in the subthreshold-PTSD group reported significantly greater anger and hostility than those in the non-PTSD group. The PTSD and subthreshold-PTSD groups did not diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
343
3
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(376 citation statements)
references
References 55 publications
(59 reference statements)
23
343
3
7
Order By: Relevance
“…In addition to studies finding strong support for the relationship between anger and PTSD in military samples, studies have also shown that Veterans diagnosed with PTSD demonstrate higher levels of anger compared with Veterans without PTSD [12,[19][20][21][22][23]. For example, Chemtob et al conducted a study in which they compared 24 Vietnam war Veterans who had been diagnosed with PTSD to 23 non-PTSD Vietnam combat Veterans and 12 noncombat Vietnam-era Veterans with psychiatric diagnoses [12].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to studies finding strong support for the relationship between anger and PTSD in military samples, studies have also shown that Veterans diagnosed with PTSD demonstrate higher levels of anger compared with Veterans without PTSD [12,[19][20][21][22][23]. For example, Chemtob et al conducted a study in which they compared 24 Vietnam war Veterans who had been diagnosed with PTSD to 23 non-PTSD Vietnam combat Veterans and 12 noncombat Vietnam-era Veterans with psychiatric diagnoses [12].…”
Section: Methodsmentioning
confidence: 99%
“…However, this study focused exclusively on Vietnam-era Veterans, raising the question of whether similar associations would be found among Veterans of other eras. More recently, Jakupcak et al examined Veterans from the Iraq and Afghanistan wars who screened positive for PTSD and compared them with those who demonstrated subthreshold levels of PTSD and those without PTSD on trait anger, hostility, and aggression [22]. Findings showed that the PTSD group reported greater anger and hostility than the subthreshold PTSD Veterans, who in turn scored higher than the non-PTSD group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jakupcak et al [24] found that Iraq and Afghanistan Veterans with PTSD reported greater aggression, anger, and hostility than Veterans without PTSD, while Lew et al [14] reported that 82 percent of OIF/OEF Veterans seen in a polytrauma clinic most frequently endorsed anger and impatience as their primary area of difficulty on the road. While this study subsequently hypothesized similar findings, this sample did not highly endorse anger on the road (only 21% endorsed very frequent anger), suggesting that "anger" may be too strong a term.…”
Section: Discussionmentioning
confidence: 99%
“…The perpetration of violence often co-presents with victimisation (Malik, Sorensen, & Aneshensel, 1997), and PTSD has been shown to be related to aggression (Dyer et al, 2009; Jakupcak et al, 2007). This association may result from an underlying dysregulation of emotion (Weiss, Tull, Viana, Anestis, & Gratz, 2012) and impulse which may cause aggression, or individuals who suffer from numbing symptoms related to PTSD may utilise aggression in order to up-regulate themselves.…”
Section: Introductionmentioning
confidence: 99%